Fungal communities in feces of the frugivorous bat Ectophylla alba and its highly specialized Ficus colubrinae diet - Chaverri Echandi, Priscila (2022)
Background: Bats are important long-distance dispersers of many tropical plants, yet, by consuming fruits, they may disperse not only the plant’s seeds, but also the mycobiota within those fruits. We characterized the culture-depend ent and independent fungal communities in fruits of Ficus colubrinae and feces of Ectophylla alba to determine if passage through the digestive tract of bats afected the total mycobiota. Results: Using presence/absence and normalized abundance data from fruits and feces, we demonstrate that the fungal communities were signifcantly diferent, even though there was an overlap of ca. 38% of Amplicon Sequence Variants (ASVs). We show that some of the fungi from fruits were also present and grew from fecal samples. Fecal fungal communities were dominated by Agaricomycetes, followed by Dothideomycetes, Sordariomycetes, Eurotiomy cetes, and Malasseziomycetes, while fruit samples were dominated by Dothideomycetes, followed by Sordariomycetes, Agaricomycetes, Eurotiomycetes, and Laboulbeniomycetes. Linear discriminant analyses (LDA) show that, for bat feces, the indicator taxa include Basidiomycota (i.e., Agaricomycetes: Polyporales and Agaricales), and the ascomycetous class Eurotiomycetes (i.e., Eurotiales, Aspergillaceae). For fruits, indicator taxa are in the Ascomycota (i.e., Dothideomycetes: Bot ryosphaeriales; Laboulbeniomycetes: Pyxidiophorales; and Sordariomycetes: Glomerellales). In our study, the diferences in fungal species composition between the two communities (fruits vs. feces) refected on the changes in the functional diversity. For example, the core community in bat feces is constituted by saprobes and animal commensals, while that of fruits is composed mostly of phytopathogens and arthropod-associated fungi. Conclusions: Our study provides the groundwork to continue disentangling the direct and indirect symbiotic rela tionships in an ecological network that has not received enough attention: fungi-plants-bats. Findings also suggest that the role of frugivores in plant-animal mutualistic networks may extend beyond seed dispersal: they may also promote the dispersal of potentially benefcial microbial symbionts while, for example, hindering those that can cause plant disease.